N-[(9-Ethyl-9H-carbazol-3-yl)methylidene]-3,4-dimethylisoxazol-5-amine - Tan, Kong Wai; Ng, S.W.; Asiri, A.M.; Khan, S.A. (International Union of Crystallography, 2010)
The azomethine double bond in the title Schiff base, C(20)H(19)N(3)O, has an E configuration. The 13-membered carbazolyl fused ring system [r.m.s. deviation = 0.023 (9) A] is nearly coplanar with the five-membered pyrazole ring [r.m.s. deviation = 0.003 (4) A]; the dihedral angle between the two systems is 10.8 (2)degrees. The crystal studied was a non-merohedral twin having a 35% minor component.